2014
DOI: 10.1073/pnas.1324189111
|View full text |Cite
|
Sign up to set email alerts
|

A disulfide tether stabilizes the block of sodium channels by the conotoxin μO§-GVIIJ

Abstract: A cone snail venom peptide, μO §-conotoxin GVIIJ from Conus geographus, has a unique posttranslational modification, S-cysteinylated cysteine, which makes possible formation of a covalent tether of peptide to its target Na channels at a distinct ligandbinding site. μO §-conotoxin GVIIJ is a 35-aa peptide, with 7 cysteine residues; six of the cysteines form 3 disulfide cross-links, and one (Cys24) is S-cysteinylated. Due to limited availability of native GVIIJ, we primarily used a synthetic analog whose Cys24 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
87
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(91 citation statements)
references
References 36 publications
3
87
0
1
Order By: Relevance
“…New frameworks can have thus been created by insertion of an extra cysteine residue either at the N-terminal end, C-terminal end, or in the core of the sequence, or by deletion of a single cysteine amino acid. Further investigation of these new conotoxin sequences could reveal novel posttranslational modifications at their unpaired cysteine residue, conferring upon them new functional advantages, as recently demonstrated with Conus geographus μO §-conotoxin GVIIJ, which is able to stabilize the sodium channel blockade (75).…”
Section: Resultsmentioning
confidence: 85%
“…New frameworks can have thus been created by insertion of an extra cysteine residue either at the N-terminal end, C-terminal end, or in the core of the sequence, or by deletion of a single cysteine amino acid. Further investigation of these new conotoxin sequences could reveal novel posttranslational modifications at their unpaired cysteine residue, conferring upon them new functional advantages, as recently demonstrated with Conus geographus μO §-conotoxin GVIIJ, which is able to stabilize the sodium channel blockade (75).…”
Section: Resultsmentioning
confidence: 85%
“…C. tessulatus venom was fractionated as described previously (41). Aliquots of pooled and individual venom fractions were assayed for activity on dissociated DRG neurons by calcium imaging.…”
Section: Methodsmentioning
confidence: 99%
“…The calcium-imaging methods have been described in detail previously (25)(26)(27)(28). The amino acid sequence of δ-conotoxin TsVIA (shown in Table 1) was determined by a combination of Edman degradation, MS/MS sequencing, and molecular cloning, as described previously (41) and in SI Materials and Methods. The amino acid sequence of δ-conotoxin ErVIA (shown in Table 1) was identified by molecular cloning as previously described (42) and by MS/MS sequencing, as described in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…Further, these toxins containing an odd-number of cysteine residues may also represent a new toxin class. A recent study identified the conotoxin, μO §-conotoxin GVIIJ, which contains seven cysteine residues where the extra cysteine was post-translationally modified and which was involved in inhibiting Na V 1-channels [75].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%